Evaluation of sputum cultures in children with spinal Muscular atrophy. (April 2023) - Levine, Hagit; Nevo, Yoram; Katz, Julia; Mussaffi, Huda; Chodick, Gabriel; Mei-Zahav, Meir; Stafler, Patrick; Steuer, Guy; Bar-On, Ophir; Mantin, Hadas; Prais, Dario; Aharoni, Sharon
Abstract: Background: Spinal Muscular Atrophy (SMA) is a severe neuromuscular disorder. Despite increased survival due to novel therapies, morbidity from respiratory complications still persists. We aim to describe these patients' sputum cultures as an expression of chronic infectious airway disease. Methods: Retrospective review of medical records of all children with SMA followed at the multidisciplinary respiratory neuromuscular clinic at Schneider Childrens' Medical Center of Israel over a 16-year period. Sputum cultures were obtained during routine visits or pulmonary exacerbations. Results: Sixty-one SMA patients, aged 1 month to 21 years, were included in this cohort. Of these, sputum cultures were collected from 41 patients. Overall, 288 sputum cultures were obtained, and 98 (34%) were negative for bacterial growth. For the first culture taken from each patient, 12 out of 41 (29%) were sterile. The most common bacteria were pseudomonas aeruginosa (PSA) (38%) and staphylococcus aureus (19.6%). PSA was found in SMA type I patients more frequently than in type II patients (15/26 = 58% vs 4/13 = 31%, p < 0.001). PSA infection was positively associated with noninvasive ventilation, recurrent atelectasis, recurrent pneumonias, swallowing difficulties, but no significant association was found with cough assist machine usage. The incidence of positive cultures did not differ between those treated with Onasemnogene abeparvovec or Nusinersen compared to those without treatment, but the age of first PSA isolation was slightly older with Nusinersen treatment (p = 0.01). Conclusions: Airway bacterial colonization is common in SMA type I patients and is not decreased by Onasemnogene abeparvovec or Nusinersen treatment. Highlights: Spinal Muscular Atrophy (SMA) in characterized in muscle atrophy and weakness. The respiratory involvement includes impaired cough and a reduced vital capacity. Despite the increased survival as a result of novel therapies, morbidity from respiratory complications still persists. Early airway colonization with a range of bacteria milieu is common in SMA patients as early as less than one month of age. Positive sputum cultures are most common in SMA type I patients, particularly with Pseudomonas aeruginosa. The prevalence of positive sputum cultures does not decrease after Nusinersen/Onasemnogene abeparvovec treatment even at an early age of treatment.